Anti-IGLON5 disease: A new case without neuropathologic evidence of brainstem tauopathy. Issue 2 (March 2020) - Erro, Maria Elena; Sabater, Lidia; Martínez, Laura; Herrera, María; Ostolaza, Aiora; García de Gurtubay, Iñaki; Tuñón, Teresa; Graus, Francesc; Gelpi, Ellen
Abstract : Objective: To describe the neuropathologic features and the molecular data of phosphorylated tau (pTau) in a new case of anti-IgLON5 disease. Methods: Review of clinical data, postmortem neuropathologic examination. Biochemical analyses of pTau were performed in brain samples from the present case and from a previously described patient with anti-IgLON5 with the characteristic brainstem tauopathy. Results: The patient was a 71-year-old man with a clinical syndrome consisting of sleep disturbance and bulbar symptoms. IgLON5 antibodies of predominant IgG4 subtype were detected in serum and CSF. He carried the HLA DRB1*10:01-DQB1*05:01 haplotype. Despite treatment with IV immunoglobulins, he unexpectedly died during sleep 2 years after disease onset. Histology showed neurofibrillary pathology and β-amyloid deposits consistent with Alzheimer disease (AD) of intermediate severity. pTau deposits were absent in the brainstem. There were few perivascular CD8 + T-cell infiltrates in the posterior hypothalamus, amygdala, and brainstem with microglial activation. The pTau immunoblot showed a pattern of bands consistent with AD, which was different from that observed in the patient with anti-IgLON5 with brainstem tauopathy who presented a differential band around 56 KDa. Conclusion: The absence of pTau deposits in the brainstem of the present patient suggests that the tauopathy of patients with anti-IgLON5 disease may be a late, secondary event. The anti-IgLON5 brainstem tauopathy has a specific molecular signature different from primary tauopathies. pTau deposits restricted to the hippocampus/limbic regions of patients with anti-IgLON5 may represent an age-related comorbidity.